Development and application of anti-immune complex antibodies for the detection of aflatoxin M1 - Saramäki, Venla (My University, 2023)
Aflatoxin M1 (AFM1) is a mycotoxin that can be found in milk or milk products derived from livestock that have eaten contaminated feed. AFM1 has toxic and carcinogenic properties to human health due to which its detection from milk products is essential. Chromatographic methods for AFM1 quantification are sensitive but generally time-consuming and expensive. With non-competitive immunoassay sensitive and easy-to-use detection methods can be obtained. The aim was to develop anti-immune complex antibodies against anti- AFM1 monoclonal antibody bound to AFM1 which can be utilized for non-competitive immunoassay. Anti-immune complex single-chain variable fragments (scFv) that bind to anti- AFM1 monoclonal antibody bound to AFM1 were selected from synthetic antibody library using phage display. In three rounds of panning, the reaction conditions were changed in terms of reaction temperature and excess amount of AFM1. From enriched phage libraries, individual scFv binders were screened in order to identify a specific immune complex binder. The highest hit rate (8.64%) was obtained from the second round of panning in which excess of AFM1 was added to washing steps as opposed to other reactions. The scFv binders were further characterized by sequencing and studying their cross-reactivity and their functionality in immunoassays. Non-competitive immunoassay for AFM1 detection was optimized regarding the antibody concentrations, number of washing steps and assay buffer with two scFv binders that showed specificity and sensitivity against the immune complex. The optimized non-competitive immunoassay exhibited EC50 values of 10.2 and 9.8 ng/ml, and the limit of detection values were 0.15 and 0.31 ng/ml for the two different immune complex binders HB6 and HH8; respectively. As AFM1 was spiked to milk recovery rates varied widely from 84% to over 120%. The immunoassay still needs optimization for it to reach regulatory limits set in the European Union legislation which is 0.05 μg/kg AFM1 in milk. In the future, this anti-immune complex antibody could be utilized for the development of lateral flow assay for rapid AFM1 detection.
Keywords: Aflatoxin M1, phage display, non-competitive immunoassay